Comparative analysis of factors affecting differences in the concentrations of gaseous anthropogenic emissions from coal and slurry fuel combustion. (15th June 2020) - Akhmetshin, M.R.; Nyashina, G.S.; Strizhak, P.A.
Graphical abstract: Highlights: Several factors have a synergistic effect on investigated anthropogenic emissions. Slurries with low S and N content can reduce NOx and SO2 by 80% vs. coal combustion. Reactions of nitrogen and sulfur reduction occur in temperature interval 800–900 °C. Sulfur turns to ash at the reaction of metals in biomass with sulfur oxides. Water concentration increasing in slurries reduces activity of NOx and SO2 . Abstract: The paper presents the results of the experimental research performed for a comparative analysis of factors that influence the concentrations of the main gaseous anthropogenic emissions from coal and waste-based slurry fuel combustion. We focus on controlling the NOx and SO2 concentrations. We have researched for the first time a group of mechanisms and factors, influencing the formation of anthropogenic emissions from burning waste as part of wet multi-component slurry fuels. The experiments were conducted with coals of different grades, coal processing waste, water-containing slurries, as well as extra additives of biomass and waste. We show how much the NOx and SO2 concentrations are affected by a wide group of factors and processes: temperature in the chamber, vaporization, initial content of sulfur and nitrogen in the fuel mixture, specialized additives with different concentrations and in different combinations, as well as specific chemical reactions in a limited range of temperatures. The experimental results show that the initial content of nitrogen in the slurry and the catalytic processes of nitrogen oxide reduction to free N2 have a dominant influence on NOx emissions due to free hydrogen radicals and interaction of additives with the components (e.g., with Fe2 O3 ). SO2 concentrations are decisively influenced by the content of sulfur in the slurry, as well as the chemical interactions of amphoteric and active metals with sulfur oxides. Combined employment of a group of factors under study can provide a reduction of NOx and SO2 by up to 80% as compared to coal combustion conditions.